2018
DOI: 10.1177/1461444818794592
|View full text |Cite
|
Sign up to set email alerts
|

Networked publics as agents of accountability: Online interactions between citizens, the media and immigration officials during the European refugee crisis

Abstract: This study examines how citizens made use of online platforms to direct diverging critiques and demands at the Finnish Immigration Service during what has come to be known as the refugee crisis in Europe. Focusing on peak periods of debate, identified using big data, we closely observe how public scrutiny of the immigration service occurred in the interactions between online users, the news media and the agency itself. Our analysis indicates that networked publics can be regarded as influential drivers of acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 33 publications
0
54
2
1
Order By: Relevance
“…Our empirical material for this study is extracted from a database of a commercial social media data analytics company, Mohawk, which extensively harvests public Finnish social media discussion at a rate of approximately 500,000 new messages per day [Pöyry et al, 2018]. As our focus was on the forms of public expertise, we decided to focus on Twitter, which is known to be the most central social media platform for political discussion and acts of communication aiming to influence political processes and public discussions [see Marttila et al, 2016;Nelimarkka et al, 2020;Vainikka and Huhtamäki, 2015], or to challenge and criticize the authorities [Ojala, Pantti and Laaksonen, 2019]. Further, it has become an important arena for communicating science to wider audiences and creating more impact for research [e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our empirical material for this study is extracted from a database of a commercial social media data analytics company, Mohawk, which extensively harvests public Finnish social media discussion at a rate of approximately 500,000 new messages per day [Pöyry et al, 2018]. As our focus was on the forms of public expertise, we decided to focus on Twitter, which is known to be the most central social media platform for political discussion and acts of communication aiming to influence political processes and public discussions [see Marttila et al, 2016;Nelimarkka et al, 2020;Vainikka and Huhtamäki, 2015], or to challenge and criticize the authorities [Ojala, Pantti and Laaksonen, 2019]. Further, it has become an important arena for communicating science to wider audiences and creating more impact for research [e.g.…”
Section: Methodsmentioning
confidence: 99%
“…We do this by exploring social media discussions concerning the actions and publicity of THL during the first months of the epidemic from January to mid-June 2020. Our empirical focus is on Twitter, which has become the most central arena for public, political discussions and debates in Finland, particularly for actors who aim to influence political decision making or challenge the authorities [Nelimarkka et al, 2020;Ojala, Pantti and Laaksonen, 2019]. Globally, Twitter has grown to be an important arena also for science communication [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…New and old forms of media intertwine in several ways, creating an interdependent hybrid media system (Chadwick, 2013: 4). Many journalists use social media as a news source, and online news stories shared through Twitter constitute important information sources for online publics (Ojala et al, 2018: 4).…”
Section: Twitter As a Public Communication Spacementioning
confidence: 99%
“…The research has demonstrated that the role of social media in the formulation of migration discourse has been rather ambiguous. On the one hand, social media has been named as one of the driving forces in the consolidation of affective publics during the refugee crisis in 2015 (Dahlgren, 2016) and as the driver of government accountability (Ojala et al, 2019). On Twitter, the general tonality of the messages containing refugee-related hashtags has been reported to be mostly positive (Coletto et al, 2016;Nerghes & Lee, 2019).…”
Section: Introductionmentioning
confidence: 99%